Comparison of the profiles of first-line PD-1/PD-L1 inhibitors for advanced NSCLC lacking driver gene mutations: a systematic review and Bayesian network meta-analysis - Fu Wenfan; Xu Manman; Shi Xingyuan; Jiang Zeyong; Zhao Jian; Dai Lu (SAGE Publishing, 2023)
Background: Numerous first-line immune checkpoint inhibitors (ICI) were developed for patients with advanced non-small cell lung cancer (NSCLC) lacking driver gene mutations. However, this group consists of a heterogeneous patient population, for whom the optimal therapeutic choice is yet to be confirmed. Objective: To identify the best first-line immunotherapy regimen for overall advanced NSCLC patients and different subgroups. Design: Systematic review and Bayesian network meta-analysis (NMA). Methods: We searched several databases to retrieve relevant literature. We performed Bayesian NMA for the overall survival (OS), progression-free survival (PFS), objective response rate (ORR), and treatment-related adverse events (tr-AEs) with a grade equal or more than 3 (grade ⩾ 3 tr-AEs). Subgroup analysis was conducted according to programed death ligand 1 (PD-L1) levels, histologic type, central nervous system (CNS) metastases and tobacco use history. Results: For the PD-L1 non-selective patients, sintilimab plus chemotherapy (sinti-chemo) provided the best OS [hazard ratio (HR) = 0.59, 95% confidence interval (CI):0.42-0.83]. Nivolumab plus bevacizumab plus chemotherapy (nivo-bev-chemo) was comparable to atezolizumab plus bevacizumab plus chemotherapy (atezo-bev-chemo) in prolonging PFS (HR = 0.99, 95% CI: 0.51-1.91). Atezo-bev-chemo remarkably elevated the ORR than chemotherapy (OR = 3.13, 95% CI: 1.51-6.59). Subgroup analysis showed pembrolizumab plus chemotherapy (pembro-chemo) ranked first in OS in subgroups of PD-L1 < 1%, non-squamous, no CNS metastases, with or without smoking history, and ranked second in OS in subgroups of PD-L1 ⩾ 1% and PD-L1 1-49%. Cemiplimab and sugemalimab plus chemotherapy ranked first in OS and PFS for squamous subgroup, respectively. For patients with CNS metastases, nivolumab plus ipilimumab plus chemotherapy (nivo-ipili-chemo) and camrelizumab plus chemotherapy provided the best OS and PFS, respectively. Conclusions: Sinti-chemo and nivo-bev-chemo were two effective first-line regimens ranked first in OS and PFS for overall patients, respectively. Pembro-chemo was favorable for patients in subgroups of PD-L1 < 1%, PD-L1 ⩾ 1%, PD-L1 1-49%, non-squamous, no CNS metastases, with or without smoking history. Addition of bevacizumab consistently provided with favorable PFS results in patients of all PD-L1 levels. Cemiplimab was the best option in squamous subgroup and nivo-ipili-chemo in CNS metastases subgroup due to their advantages in OS.